2008
DOI: 10.1016/j.foodchem.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of caprine and ovine milk proteins, brought about by aspartic peptidases from Silybum marianum flowers

Abstract: The flowers of cardoon (Asteraceae) are a rich source of aspartic peptidases which possess milk clotting activity-and are thus used in traditional cheesemaking in the Iberian Peninsula. This study was aimed at characterizing the enzymatic action of the aspartic peptidases present in flowers of Silybum marianum (L.) Gaertn. (Asteraceae), specifically upon degradation of caseins. The proteolytic activities toward Na-caseinates previously prepared from caprine and ovine milks were studied, in a comparative fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
0
12
0
7
Order By: Relevance
“…Additionally, it has been reported that a serine protease from Lactuca sativa leaves promoted clotting of skim milk as well as of milk with different fat contents (Lo Piero et al, 2002;Uchikoba & Kaneda, 1996). Aspartic protease from Oryza sativa seeds promoted cleavage of j-casein, in a pattern similar to that obtained with chymosin and pepsin (Asakura, Watanabe, Abe, & Arai, 1997), and aspartic proteases from extract of Silybum marianum flowers hydrolysed caprine and ovine milk caseins (Cavalli, Silva, Cimino, Malcata, & Priolo, 2008).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Additionally, it has been reported that a serine protease from Lactuca sativa leaves promoted clotting of skim milk as well as of milk with different fat contents (Lo Piero et al, 2002;Uchikoba & Kaneda, 1996). Aspartic protease from Oryza sativa seeds promoted cleavage of j-casein, in a pattern similar to that obtained with chymosin and pepsin (Asakura, Watanabe, Abe, & Arai, 1997), and aspartic proteases from extract of Silybum marianum flowers hydrolysed caprine and ovine milk caseins (Cavalli, Silva, Cimino, Malcata, & Priolo, 2008).…”
Section: Introductionmentioning
confidence: 60%
“…3), values that were similar to those reported by Dalgleish (1990). The degrees of casein hydrolysis by PP and chymosin were also evaluated by the reduction of a s -, b-, and j-caseins bands on SDS-PAGE, since peptides from casein proteolysis can be quantified by gel scanning, followed by densitometry (Cavalli et al, 2008;Franco, Prieto, Urdiales, Fresno, & Carballo, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Cavalli et al (2008) reported that sodium caseinate digestion from goat milk, which was hydrolyzed by Staphylococcus marianum enzymes (extract at pH 6.5, after 1 hour digestion), became intense as the reaction time passed by. Thus, considering the same reaction conditions, the longer reaction time, the greater DH degree of hydrolysis, as confirmed in our study (DH was tested at pH 6.5 for 5 hours).…”
Section: Sequencing and Profile Of Permeate (<3000da) And Retentate (mentioning
confidence: 99%
“…O trabalho realizado por Cavalli et al (2008) mostrou que a digestão do caseinato de sódio do leite de cabra, hidrolisado com peptidases aspárticas de extrato de flores Silybum marianum, a pH 6,5, foi observada após 1 hora. Porém, a digestão torna-se mais intensa com o decorrer do tempo de reação, sendo a β-caseína caprina degradada em 40%, enquanto a α s1 -caseína em 68%, após 24 horas de incubação.…”
Section: Hidrolisadounclassified
“…A maioria dos peptídeos derivados da caseína que apresentam atividade biológica é produzida in vitro pelo uso de proteinases, especialmente a tripsina (Krüger, 2006;Rossini et al, 2009). A utilização de enzimas proteolíticas para hidrólise da caseína caprina, com vistas a aplicações futuras dos peptídeos, foi relatada por Trujillo et al (1997), Cavalli et al (2008) e Santillo et al (2009), porém não foram encontrados relatos de estudos sobre a raça Moxotó.…”
Section: Introductionunclassified